2018
DOI: 10.1016/j.jor.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Wear performance of cobalt chromium, ceramic, and oxidized zirconium on highly crosslinked polyethylene at mid-term follow-up

Abstract: Patients with THA using a ceramic head and using an OxZr head were each matched to patients with a CoCr head. Mean implantation time was 5 years. There was no difference in steady state wear rate between the ceramic (0.066 ± 0.050 mm/year) and CoCr match groups (0.052 ± 0.041 mm/year), or between the OxZr (0.022 ± 0.029 mm/year) and CoCr match groups (0.048 ± 0.071 mm/year). Follow-up into the second decade will be necessary before any changes in THA wear rate from using ceramic or OxZr bearings may be appreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
4
1
1
Order By: Relevance
“…With regard to the head material we find values close to 5% in the statistical significance, although prior studies such as Sato with p = 0.45 [ 42 ], Garvin with p = 0.58 [ 43 ], or Teeter with p = 0.32 [ 44 ] do not suggest a relationship between this variable and wear risk. Our results seem to suggest that there is less wear risk in ceramic head material than in metallic.…”
Section: Discussioncontrasting
confidence: 52%
“…With regard to the head material we find values close to 5% in the statistical significance, although prior studies such as Sato with p = 0.45 [ 42 ], Garvin with p = 0.58 [ 43 ], or Teeter with p = 0.32 [ 44 ] do not suggest a relationship between this variable and wear risk. Our results seem to suggest that there is less wear risk in ceramic head material than in metallic.…”
Section: Discussioncontrasting
confidence: 52%
“…Ceramic femoral heads have been used for decades to decrease PE wear in articulation with ultra-high molecular weight polyethylene (UHMWPE) [ 25 ]. However, different femoral head materials in articulation with HXLPE have not yet been shown to affect the wear rate [ 26 , 27 ]. The results of the present study are in line with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, veneering metallic surfaces with DLC or TiN could provide a protective barrier against corrosion and wear, increasing the long-term performance of the contacting TMJ TJR surfaces. Also, the high-strength ceramic condyles could be an alternative to avoid the corrosion issue [78]. However, the microstructure integrity (i.e., absence of defects) and low roughness of the modified surfaces should be controlled to promote such low friction effect.…”
Section: Degradation Of Tmj Tjr Componentsmentioning
confidence: 99%
“…This has subsequently been shown to cause oxidative degradation of the polymer both in vitro and in vivo leading to an increased wear rate and release of polymeric debris [79,80]. Some studies have reported a lower friction when a highly cross-linked polyethylene (XLPE) counter-body was used instead of UHMWPE against CoCr-based surfaces [78,81]. Contrarily to hip and knee prostheses, only a few studies are available that describe the tribocorrosion behavior and biological response of novel advancements in TMJ TJR prostheses [4,19,45,82].…”
Section: Degradation Of Tmj Tjr Componentsmentioning
confidence: 99%